Wilayah Perdesaan Berkelanjutan: Suatu Eksplorasi Teoritis - Prabatmodjo, Hastu (Journal of Regional and City Planning, 2006)
Since its formulation in the Brundtland Report, sustainable development has gained global attention. Despite its philosophical simplicity, subtantial efforts have to be undertaken to implement this concept because of its practical complexity. One of the most challenging issues is how to implement it in the context of rural region in developing countries. This paper clarifies the meaning of sustainable rural region and introduces some idea how to implement the concept. Sustainable development relies on the balance among economic, social and ecological objectives. In rural region, the success in managing environmental stressors and poverty is very important for implementing the concept. Its implementation requires different approaches that can be distinguished based on the economic and ecological characteristics of rural region.